Gairah Diujung Syahadat - M Lufi Fakhri; Nerosti Nerosti (SENDRATASIK UNP, 2020)
The creation of the dance called "Gairah Diujung Syahadat" aims to create creative dance work by expressing ideas which originated from life problems of a young person who converted his belief because he wanted to marry a Minangkabau woman. This dance work entitled "Gairah Diujung Shahadat" belongs to dramatic dance. The presentation form in the dance work "Gairah Diujung Syahadat" is symbolic representational. The dance work "Gairah Diujung Syahadat" is inspired by the social phenomena of life where a young man met a woman in a night life and wanted to marry her. The young man struggleduntil he converted his belief andsaid the creed. After this young man got the women, he did not dothe obligations in his creed. Everyone judged him so that he realized that he could not joke the belief, and he had to return to the right path. The dance work "Gairah Diujung Syahadat" focuses on an incident or event. It is an interpretive expression of the struggle of a young man, but the young man does not consider the impact of his actions for goodness in terms of belief.  The work is manifested through movement, stage setting, make-up, costume, lighting, and is emphasized by music.